University Infrastructure Quality and Students Engagement at a Private University in Uganda - Mugizi, Wilson (Interdisciplinary Journal of Education Research, 2021)
This study assessed the influence of university infrastructure quality on students’ engagement at the western branch of a private University in Bushenyi District, Uganda. Particularly, the study assessed the influence of lecture rooms infrastructure, university-level infrastructure and university utilities. Using the positivist approach, the study was guided by the correlational research design, collecting data using a questionnaire on a sample of 183 students. Descriptive analysis revealed that student engagement was high, and lecture rooms’ infrastructure and university utilities good. However, the students rated university-level infrastructure as fair. Regression analysis showed that lecture rooms’ infrastructure and university utilities were significant positive predictors of students’ engagement. However, university-level infrastructure had a positive but insignificant influence on students’ engagement. Thus, the quality of lecture rooms’ infrastructure is imperative, university utilities are essential and improved University level infrastructure is a requirement for enhancing students’ engagement. Therefore, it was recommended that universities emphasize providing quality to classroom infrastructure, improve university-level infrastructure, and establish quality university utilities.
Keywords: Lecture rooms infrastructure; Quality; Student Engagement; University Level Infrastructure; Utilities